PENGARUH KONFLIK PERAN GANDA DAN STRESS KERJA TERHADAP KINERJA PERAWAT RUMAH SAKIT UMUM DR. M. HAULUSSY AMBON - Tjokro, Cythia Imelda; Asthenu, Jean Rosa (Arthavidya Jurnal Ilmiah Ekonomi, 2015)
This study aimed to analyze the effect ofrole conflict consisting ofwork-family conflict and family-work conflict on job stress and jobperformance of nurses from dr. M.Haulussy hospitals general Ambon. Thisresearch was conducted in dr. M.Haulussy hospital Ambonfor two months. Theresearch data was collected through a questionnaire, which is then processedand analyzed using SPSS 19 with path analysis techniques.The results showedthat work-family conflict (X1) and significant positive effect on job stress (Y1)nurse of dr. M.Haulussy hospital Ambon. Family-work conflict (X2) positiveand significant impacton job stress (Y1) nurse of dr. M.Haulussy hospitalAmbon. Job stress (Y1) negatively affect the performance of nurses (Y2) dr.M.Haulussy hospital Ambon. Work-family conflict (X1) negatively affect theperformance of nurses (Y2) dr. M.Haulussy hospital Ambon. Family-workconflict (X2) negatively affect the performance of nurses (Y2) dr. M.Haulussyhospital Ambon. Thus all the hypotheses proposed in this study can beaccepted.Keywords: dual role conflict, job stress, performance nurses